The Effects of Crude Oil Spill on Some Soil Properties of Different Sites in Duhok Governorate-Kurdistan Region of Iraq - Hashim, Farhad A. (Science Journal of University of Zakho, 2019)
A study was conducted to investigate the impact of oil spillage on some properties of soils collected from Kashe and Nzarke sites in Duhok governorate, Kurdistan region of Iraq. Soil samples were taken from each site after one weak and then after three months at 0-15 cm and 15-35 cm depths with control samples approximately 500 m from outside oil spill area. The soil samples were analyzed using standardsof routine laboratory methods to determine some soil properties. Based on results of the study the contaminated area has higher % TN (percentage total nitrogen) (0.34 and 0.28 %), % TOC (percentage total carbon) ( 4.84 and 5.81 %), Pb (lead) (1.59 and 2.28 mg L-1) and Fe (Iron) (3.20 and 3.13 mg L-1) for Kashe and Nzarke sites respectively than the control especially for 0-15 cm. Crude oil causes decrease in soil pH below 8.2 and also reduced the concentration of available phosphorus to a values of (18.40 and 15.20 mg L-1) for Kashe and Nzarke soils respectively than the control (20.60 and 16.20 mg L-1) for the two sites respectively. Higher values for EC (electrical conductivity), % TN, available phosphorouswere found in Kashe site while Nzarke had higher % TOC, % OM (organic matter), CEC (cation exchange capacity), THC (total hydrocarbon) and available phosphorus.
Keywords: Crude oil spill; Heavy metals; Soil properties; Total hydrocarbons